Climate-related disclosure commitment of the lenders, credit rationing, and borrower environmental performance - Iftekhar Hasan; Haekwon Lee; Buhui Qiu; Anthony Saunders (Bank of Finland, 2023)
Using lenders becoming members of the Task Force on Climate-Related Financial Disclosures (TCFD) as a plausible exogeneous shock, we examine whether and how lenders' commitment to transparent climate-related disclosures affects borrower firms' environmental performance. We find that client firms of TCFD-member lenders, relative to control firms, significantly improve their environmental performance after the TCFD launch. The effects are stronger for polluting firms. Moreover, TCFD-member lenders influence their borrowers' environmental performance via charging higher loan spread and reducing the number and amount of new loans issued to polluting firms. Finally, polluting clients of TCFD-member lenders experience tightened financial constraints subsequently.
Keywords: G21; G30; Q54; 330; Climate-related Disclosure Commitment; Credit Rationing; Borrower Environmental Performance